Health seeking behaviour in elderly hypertensive patients: a hospital based study - Jain, Jitendra; Sinha, Umesh (International Journal of Medical Research and Review, 2015)
Background: Hypertension is now widely prevalent in several developing countries particularly those in rapid transition and is affecting both the elderly and middle aged alike. Prior studies have shown that anti-hypertensive drug treatment for older hypertensive persons confers highly significant and clinically relevant reductions in cardiovascular morbidity and mortality rates. Nevertheless, a considerable percentage of older persons with hypertension are not detected or are not adequately treated for hypertension. Material and Methods: A Hospital-based cross-sectional study was carried out in the Department of Medicine of Chirayu Medical College and Hospital, Bhopal located in central India. A pretested and pre-structured oral questionnaire was used to interview the subjects and to collect data on demographic characteristics, health seeking behaviour and expenditure on treatment for hypertension (in previously diagnosed cases). Results: All the elderly hypertensives were visiting the doctor at least once in a month. 80% of the hypertensives had their BP checked once in 15 days. Out of total patients, 60% reported that they missed at least single dose in the last one month period. 8% reported that they skipped their medicine for more than 7 days due to some reasons. Conclusion: urgent steps to improve health education and health promotion (specifically on modifiable risk factors and awareness of BP) measures have to be made by the policy makers on a large scale.